A significant role of permeability on blood flow for hybrid nanofluid through bifurcated stenosed artery: Drug delivery application. (April 2020) - Shahzadi, Iqra; Bilal, S.
Highlights: Permeability impacts are more effective to reduce the impacts of hemodynamics for atherosclerotic artery having bifurcation effects. For daughter artery, the shear stress is reduces for bifurcation angle while for parent artery the opposite trend is observed. In bifurcated region, the number of circulating bolus increases for stiffness, rigidity and damping parameter whereas bolus size reduces in stenotic region. Profiles of velocity exhibit higher results for hybrid nanofluid in comparison to Cu-blood and pure blood cases. Abstract: Objective: The prime objective of concerned article is to discuss the permeability impacts on blood flow by considering hybrid nanofluid through bifurcated stenosed artery. Design/approach: The human body circulatory framework involves the arrangement of veins that fuse the bifurcation on parent, at apex and on regions of daughter artery with nanoparticles is viewed. Blood streaming is recognized as Newtonian along vessel segment. The walls of the stenosed bifurcated artery is considered to be permeable as well as compliant. Copper and its oxide as used as drug to minimize the stress and the lesions of the atherosclerotic artery. Findings: The theoretical investigation is carried out by invoking the experimental values of hybrid nanoparticles into the structured equations. Moreover, impacts of hemodynamics are also make sense of to inspect the progression of blood for atherosclerotic vein. Daughter and parent artery comparison is described through parabolic graph of velocity. Graphical illustration is utilized to present the theoretical results of this drug delivery model. Metallic nanoparticles justify their use in drug delivery. Conclusions: The flow of blood is viewed as not quite the same as pressure between segments of atherosclerotic and non-atherosclerotic course. Bifurcation angle minimize the stress for daughter artery whereas trend is opposite for parent daughter. The change in compliant wall parameter reduces the circulating bolus size for parent daughter whereas for daughter artery the change in bolus shape is observed.